Surgical Outcome in Patients with Ruptured Sinus of Valsalva: A 5 Year Experience at a Tertiary Care Center of Middle Income Country (Medical Forum Monthly, 2021)
Objective: To evaluate the surgical outcomes in patients with ruptured sinus of valsalva who presented at a tertiary care center of middle income country.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at National Institute of Cardiovascular Diseases Karachi from June 2016 to May 2021 for the period of five years.Materials and Methods: After approval from the ethical review committee of the institution, hospital records of the patients fulfilling the inclusion criteria were accessed. Inclusion criteria for the study are patients who presented with the diagnosis of ruptured sinus of valsalva on echocardiography and undergone surgical treatment. After quality assessment of the data, IBM SPSS version 21.0 was used for the analysis. The continuous variables were summarized as mean ± SD (standard deviation) and categorical response variables were expressed as percentages.Results: 30 patients with ruptured sinus of Valsalva were diagnosed on Transthoracic echocardiography and undergone surgical treatment. Out of 30 patients, 18 (60%) were males and 12 (40%) were females. The mean age was 26.6 years (range:16 to 47 years). Typical “wind sock” were present in 24(80%) on echocardiography. The aneurysm had communication with right ventricle outflow tract in 28(93%) patients while in 2 (7%) patients its communication was between the no coronary cusps and the right atrium. Twenty-five patients (83.3%) had associated VSD. Five (16.6%) patients had some element of aortic valve incompetence ranging from mild to moderate. In hospital mortality was 0%. All patients survived and were discharged from hospital without any significant morbidity.Conclusion: Ruptured Sinus of Valsalva is a surgical emergency. The surgical outcomes in these patients are encouraging with good survival and low complication rate.